The Effectiveness Of Saline Nasal Spray Therapy On Changes In Nasal Mucociliary Transport Time In Patient With Allergic Rhinitis - Subagiarta, I Komang A; Hadi, Wiyono; Isbandiati, Endang (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction: Treatment for allergic rhinitis as a disease that can impact on the quality of life, work productivity, school performance, and disturbances in the physiological function of the nose with recurring symptoms need more effective treatment. Nasal wash solution with isotonic saline in nasal spray method (Saline Nasal Spray) is known to reduce the symptoms of allergic rhinitis by clearing secretions, reduces edema, and remove harmful ingredients that go along with breathing air. The purpose of this study ledge used for the effectiveness of Saline Nasal Spray to changes in nasal mucociliary transport time patients with allergic rhinitis. Methods: Experimental research of pre-post test with control group design. Mucociliary transport time was measured using the saccharine test 20 samples in the group treated with saline nasal spray treatment and 20 samples in the control group without saline nasal spray. Result: Based on the analysis, Mann-Whitney for the treatment group and the control group obtained significant results p = 0.000 (p